Evaluating the Performance of Indian Banking Sector using Data Envelopment Analysis during Post-Reform and Global Financial Crisis - Kumar, Mukesh (2012)
Enticed by the reform of Indian banking sector in the early 1990s and further slowdown in the economy as a result of global financial crisis in late 2000s, the current study analyzes the performance of Indian banks using data envelopment analysis. The performance is measured in terms of technical efficiency, returns-to-scale, and Malmquist productivity index for a sample of 33 banks, consisting of 19 public sector and 14 private sector banks during the period spanning 1995-96 to 2009-10. The jackknifing analysis, followed by the dummy variable regression model is used to identify the outlier and its possible impact on overall efficiency trends. Findings reveal that efficiency scores are robust in the sense that the inclusion of outlier does not affect the overall efficiency trends. The public sector bank is faintly doing better than the private sector banks in terms of (i) technical efficiency since 2003-04 and (ii) scale efficiency from 2000-01 onwards. There is growing tendency of public banks operating under increasing returns to scale, implying that substantial gains could be obtained from altering scale via either internal growth or consolidation in the sector. The difference in the Total Factor Productivity (TFP) change between these two types of banks is found to be statistically significant in favour of public sector banks. The technological change has been the dominating source of productivity growth, whereas, the contribution of pure efficiency change and scale change are found to be negligible in Indian banking sector during the period of study. The reform in Indian banking sector has clearly re-energized the Indian banking sector as a whole, resulting in a positive change in TFP through technological change possibly as a result of adoption of latest technology and new business practices in post reform period. However, there is evidence of shrink in the market resulting in movement of the banks towards increasing returns-to-scale as well as negative growth in TFP in both the sectors during the period of global financial crisis.